How Do Airlines Cut Fuel Usage, Reducing Their Carbon Emissions? - Jan K. Brueckner; Matthew E. Kahn; Jerry Nickelsburg (Center for Economic Studies and ifo Institute (CESifo), 2023)
Airline fuel consumption is costly for the firms and for society as well due to a climate-change externality. We study how fuel price changes affect cost-minimizing choices by airlines that have implications for the extent of this externality. The airline industry's capital stock can be easily inventoried as a set of long-lived, durable aircraft. This portfolio approach allows us to study the utilization and composition of the capital stock at a highly disaggregated level. Changes in airline operations directed toward conserving fuel can be an important path toward lower emissions.
Keywords: Q52; L93; 330; airlines; fuel; climate change; carbon emissions